Phosphatidic Acid: From Pleiotropic Functions to Neuronal Pathology - Tanguy, Emeline; Wang, Qili; Moine, Hervé; Vitale, Nicolas (Frontiers in Cellular Neuroscience, 2019)
Among the cellular lipids, phosphatidic acid (PA) is a peculiar one as it is at the same time a key building block of phospholipid synthesis and a major lipid second messenger conveying signaling information. The latter is thought to largely occur through the ability of PA to recruit and/or activate specific proteins in restricted compartments and within those only at defined submembrane areas. Furthermore, with its cone-shaped geometry PA is able to act as a modulator of membrane shape and has thus been proposed to play key functions in membrane trafficking events, especially in membrane fusion and fission steps, where lipid remodeling is believed to be crucial. These pleiotropic cellular functions of PA, including phospholipid synthesis and homeostasis together with important signaling activity, imply that perturbations of PA metabolism could lead to serious pathological conditions. In this mini-review, after outlining the main cellular functions of PA, we highlight the different neurological diseases that could, at least in part, be attributed to an alteration in PA synthesis and/or catabolism.